1998
DOI: 10.1159/000044934
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition of Platelets in Patients with Uremia

Abstract: Aims: The lipid composition of platelets and the function of these cells in patients with uremia were studied. Methods: Fourteen patients and 14 normal volunteers were studied. Platelet lipids including phospholipids and cholesterol, as well as the platelet aggregation response to agonists, were studied. Results: The amount of platelet phospholipids was decreased in patients compared to controls (338.0 ± 79 vs. 511.6 ± 125 nmol/109 cells; p < 0.001), while the percentage of the five main specimens o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although this metal does not display redox capacity, it is capable of inducing peroxidation in cerebral tissue (8) and platelet aggregation in vitro (13). In addition, a high level of this metal is also associated with pathologies such as Alzheimers encephalopathy, amyotrophic lateral sclerosis and ageing (28,29). Vecino et al (29) reported an increase in the cholesterol/phospholipid ratio in the platelets of uremic patients, which was correlated with a hyperreactive state, even though a platelet hypofunction was detected in vitro.…”
Section: Results Ands Discussionmentioning
confidence: 99%
“…Although this metal does not display redox capacity, it is capable of inducing peroxidation in cerebral tissue (8) and platelet aggregation in vitro (13). In addition, a high level of this metal is also associated with pathologies such as Alzheimers encephalopathy, amyotrophic lateral sclerosis and ageing (28,29). Vecino et al (29) reported an increase in the cholesterol/phospholipid ratio in the platelets of uremic patients, which was correlated with a hyperreactive state, even though a platelet hypofunction was detected in vitro.…”
Section: Results Ands Discussionmentioning
confidence: 99%
“…We also identified genes involved in lipid metabolism, such as glycine N-acyltransferase-like 2 (GLYATL2), phospholipase C eta 1 (PLCH1), phosphatidylcholine transfer protein (PCTP), OSBP2 and SERINC1, whose levels are deregulated in uremic conditions. This may partially explain the altered synthesis of bioactive lipids (40,41) and membrane lipid composition (42,43) observed in platelets of uremic patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that the incidence of HIT antibodies in patients receiving chronic hemodialysis is less than in patients receiving dialysis in the acute setting. 18,19 As HIT is frequently associated with potentially life-threatening thrombotic events, discontinuation of heparin treatment and initiation of alternative anticoagulation is considered mandatory. Heparin must not be added to any flushing solution, and heparin-coated systems should not be used.…”
Section: Discussionmentioning
confidence: 99%